The Effects of Regulatory Lipids on Intracellular Membrane Fusion Mediated by Dynamin-Like GTPases - Moon, Yeojin; Jun, Youngsoo (Frontiers in Cell and Developmental Biology, 2020)
Membrane fusion mediates a number of fundamental biological processes such as intracellular membrane trafficking, fertilization, and viral infection. Biological membranes are composed of lipids and proteins; while lipids generally play a structural role, proteins mediate specific functions in the membrane. Likewise, although proteins are key players in the fusion of biological membranes, there is emerging evidence supporting a functional role of lipids in various membrane fusion events. Intracellular membrane fusion is mediated by two protein families: SNAREs and membrane-bound GTPases. SNARE proteins are involved in membrane fusion between transport vesicles and their target compartments, as well as in homotypic fusion between organelles of the same type. Membrane-bound GTPases mediate mitochondrial fusion and homotypic endoplasmic reticulum fusion. Certain membrane lipids, known as regulatory lipids, regulate these membrane fusion events by directly affecting the function of membrane-bound GTPases, instead of simply changing the biophysical and biochemical properties of lipid bilayers. In this review, we provide a summary of the current understanding of how regulatory lipids affect GTPase-mediated intracellular membrane fusion by focusing on the functions of regulatory lipids that directly affect fusogenic GTPases.